Perinatal HIV-infection in Sankt Petersburg and Modern Therapy Concomitant Viral Infections - V. N. Timchenko; E. B. Yastrebova; O. V. Bulina (Детские инфекции (Москва))
The study included 338 HIV-infected children (B-23) and 350 children with perinatal contact HIV infection (R-75), consisting on the dispensary in the department of maternal and child the St. Petersburg City AIDS Center. In 32 persons (9.5%) diagnosed with secondary infections. In the structure of viral opportunistic infections (herpesvirus, SARS) amounted to 39.8%, bacterial (bronchitis, tonsillitis, pyoderma, tuberculosis) — 34.8%, fungal and parasitic (candidiasis of the oral mucosa, PCP) — 25.4 %. Combined therapy (causal, pathogenetic, symptomatic) SARS in children with B-23 and R-75, allows you to get in early (6th d. Treatment) regress the main symptoms of acute respiratory diseases. Modern therapy of congenital cytomegalovirus infection (VTSMI) in children with B-23 and R-75 of the first year of life with antitsitomegalovirusnogo immunoglobulin and preparation of human recombinant interferon alfa-2b in the form of rectal suppositories — VIFERON, causes persistent normalization of clinical and laboratory parameters.